Da métrica à estética do cosmos - Bergamo, Mauricio Sergio (2021)
The main objective of study of this Doctoral Thesis in Geography is the concept of nature. The investigations start from the theoretical studies that consider two paradigms, prominently significant, regarding the formalization of the Western worldview, to know: one supported by rational aspects and by numbers; the other one based on emotional and aesthetic countenances. The first being quantitative-cosmo-paradigm. The epistemological assumptions that built the Modern Science, the philosophical propositions of the Enlightment, and important historical events in the West that marked the measurement and the notion of utility of nature's ontological statutes. The second is the cosmo-paradigm-qualitative. The artistic sets of intellectuals, who belonged to the German Romanticism and Classicism, are analyzed to highlight the qualitative countenances of nature. One of the main marks of the quantitative paradigm, besides the consistent worldview to a mechanical gear and the notion of the utility of the natural resources to the technical-scientific-economic development of the European countries, is the rupture between the subject and the object, caused by the Mathematics, through the experimentation of natural phenomena and the philosophical instrumentalism of reason. On the other hand, the qualitative paradigm craves the direct link between the subject and the object through the contemplation of nature's phenomena, the appreciation of the Arts and the Aesthetical Philosophy on issues related to the unveiling of cosmic events. In both paradigms, theories of well-known thinkers, mathematicians, scientists, and philosophers are brought up, together with the literary and artistic thinking of renowned names of Western poetry, painting and dramaturgy. Epistemic inheritance of de Copernicus, Kepler, Galileu, Newton, Francis Bacon, Descartes, Diderot, Buffon, Voltaire, Kant, Fichte, Schelling, Schiller and Goethe, in the same way as the artistic legacy of Caspar David Friedrich, Jacob Philipp Hackert, Jacob van Ruisdael, Rebrant van Rijin and Cláudio de Lorena, are redemptions to ensure the dialectical analysis between the quantitative and qualitative cosmo-paradigm. From this relation, some protagonists appear. The representatives, the prototypes of each of the paradigms: Homo Faber and the Genius/Artist. The historical and epistemological itinerary, carried out in the course of these theoretical arguments, by enabling the encounter between two different ways of conceiving the nature, allow the epistemological foundation of the Synthesis, which objects to confirm two important concepts elaborated by the author: the absolute knowledge and the symmetricorganic of nature. Considering the notes undertaken in the first and seconds parts, in the third part have as theoretical support the Works of Alexander von Humboldt, a peculiar idea of nature is presented, in which the quantitative and qualitative aspects, the reason and emotion, and finally, the subject and the object are inextricably related, to formalize an image of an integral and unitary nature.